"I Think Parents Shouldn't Be Too Pushy": A Qualitative Exploration of Parent and Youth Perspectives of Youth Decision-Making Involvement in Starting Continuous Glucose Monitoring. Issue 5 (October 2021) - Fremont, Ettya R.; Slick, Nathalie; Willi, Steven M.; Miller, Victoria A.
Purpose: The purpose of this qualitative study was to explore parent and youth perspectives of the decision-making process to start continuous glucose monitoring (CGM). Methods: Youth with type 1 diabetes and their parents were assessed with semistructured interviews before adding CGM to their regimen and 2 months after device initiation. Interviews focused on parent, youth, and provider decision-making roles and suggestions for enhancing youth decision-making involvement (DMI). Data were coded and analyzed using thematic analysis. Results: Youth (N = 41; 13.7 ± 2.9 years) were categorized into decision-making roles: (1) youth primary decision maker (54.8%), (2) youth primary decision maker with parental influence (14.3%), (3) parent primary decision maker with youth agreement (26.2%), and (4) parent primary decision maker without youth agreement (4.8%). Participants described that clinicians provided information, recommended CGM, and gave support. Recommendations to enhance youth DMI included that youth should ask questions, express opinions, and do their own research. Providers should give unbiased information and use visual aids (eg, show the device and videos) to engage youth. Conclusions: Participants agreed that whereas youth should have a primary role in the decision about CGM, parental and provider support is critical. Parents and providers can facilitate dialogue by directly engaging with youth about their thoughts, feelings, and concerns. Provider use of visual aids may enhance youth engagement and expectations.